Therapeutic effect of topical application of curcumin during treatment of radiation burns in a mini-pig model - Kim, Joongsun (J Vet Sci, 2016)
Curcumin protects the skin against radiation-induced epidermal damage and prevents morphological changes induced by irradiation skin, thereby maintaining the epidermal thickness and cell density of basal layers. In this study, the effects of topical curcumin treatment on radiation burns were evaluated in a mini-pig model. Histological and clinical changes were observed five weeks after radiation exposure to the back ((60)Co gamma-radiation, 50 Gy). Curcumin was applied topically to irradiated skin (200 mg/cm(2)) twice a day for 35 days. Curcumin application decreased the epithelial desquamation after irradiation. Additionally, when compared to the vehicle-treated group, the curcumin-treated group showed reduced expression of cyclooxygenase-2 and nuclear factor-kappaB. Furthermore, irradiation prolonged healing of biopsy wounds in the exposed area, whereas curcumin treatment stimulated wound healing. These results suggest that curcumin can improve epithelial cell survival and recovery in the skin and therefore be used to treat radiation burns.